IMPLIKASI BIAYA DAN MANFAAT PELAKSANAAN SVLK TERHADAP SEKTOR PERKAYUAN SKALA KECIL - Satria Astana; Krystof Obidzinski; Wahyu Fathurrahman Riva; Gladi Hardiyanto; Heru Komarudin; Sukanda Sukanda (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2014)
In 2009, Indonesia decided to make the implementation of the Timber LegalityVerification System (SVLK) mandatory for all timber enterprises in order to ensure full legality compliance of Indonesia timber. This decision was intended to remove any doubts about the legality of the Indonesian timber traded internationally. SVLK was also designed to become the basis for the Voluntary Partnership Agreement (VPA) between the European Union and Indonesia. In September 2013,VPA was finalized and SVLK officially became its cornerstone. However, there are serious problems with implementing SVLK system. In the large-scale timber sector, achieving SVLK compliance may not be a big problem. However, small-scale timber enterprises face numerous challanges. This study examines the obstacles preventing the progress with SVLK in the small-scale sector, particularly the cost and benefit implications. The necessary data were collected through stakeholder interviews and field observation in timber business units. The study concludes thatSVLKcertification carries significant additional costs for small-scale timber sectors with little improvement of benefits.We recommend the Ministry of Forestry and other relevant institutions should simplify SVLK implementation requirements for small scale timber enterprises and guard against a potential drop in competitiveness of the small-scale timber exports due to additional costs.